(untitled) (Journal of Material Science and Technology Research, 2023)
Abstract: Usages of various chemical substitution schemes of the initial multiferroic BiFeO3 can significantly reduce known drawbacks specific for the functional oxides based of iron ions and thus foster a creation of novel magnetoelectric compounds perspective for various technological applications. In the present study the co-doped compounds of the system Bi1-y(Ba1- xSrx)yFe1-yTiyO3 (x = 0.0 – 1.0; y ≤ 0.4) synthesized using sol-gel technique were analyzed focusing on the crystal structure stability and the correlation between the structure and magnetic properties. The concentration driven evolution of the crystal structure as well as the unit cell parameters were investigated based on the X-ray diffraction data, the correlation between the crystal structure and the magnetic properties of the compounds has been studied by magnetometry techniques. The compounds Bi1-y(Ba1- xSrx)yFe1-yTiyO3 with x = 0; y = ≤ 0.2 are characterized by single-phase rhombohedral structure, and increase in the dopant concentration to y = 0.4 leads to the stabilization of the pseudocubic phase. An increase in the Sr content leads to the phase transition in the compounds to the single phase state with the cubic structure which is accompanied by an increase in the value of the remanent magnetization.